Modulação autonômica da freqüência cardíaca de homens saudáveis e pacientes com disfunções cardiorrespiratórias crônicas - Reis, Michel Silva (2007)
The changes on the heart rate sympathetic-vagal balance caused to chronic obstructive pulmonary disease or chronic heart failure, as well as, the hemodynamics change induced by the non-invasive ventilation were unclear. In this context, we proposed to develop two studies. The first study was titled by The heart rate autonomic control in chronic obstructive pulmonary disease and chronic heart failure patients on the rest and during the respiratory sinusal arrhythmia maneuver . The purpose of this study was to evaluate the heart rate (HR) autonomic modulation in chronic obstructive pulmonary disease (COPD) patients as well as chronic heart failure (CHF) patients on the rest as well as during the respiratory sinus arrhythmia maneuver (M-RSA); and to correlation the HR autonomic modulation and seriousness levels of both pathologies. Twenty-seven male volunteers were subdivided in three groups: ten presented COPD (69±9 years); seven presented CHF (62±8 years) and; ten were healthy with 64±5 year-old (control). When resting, the three groups electrocardiography signal was obtained in three conditions: 1) lying position for 15 min; 2) lying position during the M-RSA for 4 min; and 3) sitting position for 15 min. The data was analyzed by the time (RMSSD and SDNN indexes) and the frequency domain, in total power, low frequency, high frequency absolute (ab) and normalized (nu) units and LF/HF ratio. Regarding the M-RSA indexes, the expiratory/inspiratory ratio (E/I) and the inspiratory/expiratory difference (∆IE) were calculated. The main results showed that the CHF and the COPD patients presented lower E/I ratio values (0,03±0,01 vs 0,09±0,04 e 0,04±0,02 vs 0,09±0,04) and ∆I/E values (0,67±0,13 vs 1,09±0,13 e 0,81±0,20 vs 1,09±0,13), when compared to control group. Strong correlations were observed between the forced expiratory volume in the first second (FEV1) and the RMSSD (r=-0,73) and between the FEV1 and the BF absolute (r=-0,71) in the COPD patients. At same, strong correlations were observed between the ejecting fraction and the RMSSD (r=0,83) in CHF patients. Concluding, the results of this study suggest that both, the COPD and the CHF patients, presented parasympathetic activity reduction and there is a relation between the seriousness levels of both pathologies and the HR autonomic activity. The second study was titled to The acute effects of the continuous positive airway pressure (CPAP) in the heart rate autonomic control of chronic obstructive pulmonary disease and chronic heart failure patients . The purpose of this study was to evaluate the acute continuous positive pressure airway over the heart rate (HR) autonomic control and the respiratory variables behavior in COPD as well as CHF patients. Twenty-eight male volunteers were sub-divided in three groups: ten presented COPD (69±9 years); eight presented CHF (62±8 years) and; ten were healthy with 64±5 year-old (control). The electrocardiography signal was obtained for 10 min in the sitting position with spontaneous breath (SB) and following randomly conditions: CPAP Sham, CPAP 5, and CPAP 10 cmH2O. Additionally, the breath rate, the endtidal of carbon dioxide, and the peripheral oxygen saturation were obtained. The HR and it variability data were analyzed by the time and the frequency domain, in according with previous describe. The main results showed that the ETCO2 reduced in all groups during the CPAP application. COPD group were significantly lower values of the RMSSD index in the Sham (1.06), CPAP 5 (1.08), and CPAP 10 (1,01) than SB (1,22). In addition, they presented increased in the LFnu (1.60 vs 1.82) and decreased in the HFab (1.90 vs 1.55) from the SB to CPAP 10. The CHF group RMSSD index and TP increased to SB (1.31 and 2.62) to CPAP 5 (1.44 and 2.87) and the CPAP 10 (1.48 and 2.97), respectively. Concluding, the CPAP caused modification in the HR autonomic control and improvement in the alveolar ventilation of COPD, CHF patients and healthy individuals.